ANALISIS KOMPOS SAMPAH ORGANIK DAN APLIKASINYA TERHADAP ANAKAN GAHARU - Yulian Atkana; Rima H. S. Siburian; Alce Noya (EnviroScienteae, 2019)
Organic waste of public market is one of the problems that greatly impact public health. The technology of processing public market waste into compost is a very good alternative, yet how long does it take, to process into compost and any nutrient contained requires research on this matter, as well as its application to plants, in this case, agarwood. The method used in this study was the experimental method with the old treatment of compost formation, as well as its application to agarwood plant using a completely randomized design (CRD). The results showed that 28 days of composting contained nutrients in the form of ions which were more easily absorbed by plants compared to nutrient content at duration 7 days. This is supported by the application of compost, where the addition of compost is very influential on the height of agarwood. As such, compost from organic ingredients is very well applied to agarwood plant.